Treating acid mine drainage with decomposed organic soil: Implications for peatland rewetting. (1st June 2022) - Roesel, Lydia K.; Zak, Dominik H.
Abstract: Acidification and salinisation of groundwater and surface water bodies are worldwide problems in post-mining landscapes due to acid mine drainage (AMD). In this study, we hypothesised that highly decomposed peat offers a suitable substrate for mitigating AMD pollution of water bodies and that hydraulic load affects the removal efficiency of iron and sulphate. A lysimeter experiment was conducted mimicking peatland rewetting to quantify iron and sulphate removal and pH changes at different loading rates. The low initial pH of 4 rose to 6 and electrical conductivity declined by up to 47%. The initially high concentrations of iron (>250 mg/L) and sulphate (>770 mg/L) declined by, on average, 87 and 78%, respectively. The removal efficiency of sulphate was negatively correlated with either the hydraulic or the sulphate load, respectively, i. e. the lower the hydraulic load, the higher the removal efficiency of sulphate. However, the removal of iron was not explained by the load. The results imply that desulphurication and thus subsequent precipitation of iron sulphides was the main removal process and that peatland rewetting is an effective measure to mitigate AMD pollution of freshwater systems. For the heavily AMD-polluted studied section of the River Spree, we estimated by combining experimental with field data that a sulphate load reduction of the river by about 20% (36, 827 tons/yr) will occur if all peatlands in the sub-catchment (6067 ha; 6.7% of the total area) are rewetted. Future investigations must show if the pollutant removal is declining over time in decomposed peat layers due to acidification and/or lack of bioavailable carbon and how the rewetting of peatland with AMD will affect the restoration of their ecosystem functioning in the long term. Graphical abstract: Image 1 Highlights: Mining activity causes high iron and sulphate concentration in water bodies. Lysimeter experiment run with rewetted peat and acid mine drainage. Iron-II and sulphate concentrations decreased up to 91 and 87%. Lower hydraulic load leads to higher sulphate removal but not affect iron-II removal. Rewetting peatland is an effective management tool to treat acid mine drainage.